The Association Body Mass Index with the Incidence of Anaemia Among Students - Karmila Djihu; Widia Shofa Ilmiah; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Anaemia among teenagers is a significant public health concern that can adversely affect their quality of life, cognitive function, and academic performance. Nutritional status, commonly assessed using Body Mass Index (BMI), is suspected to influence the risk of developing anaemia. This study aims to analyse the relationship between BMI and the incidence of anaemia among students at Senior High School II Rilamuta. The primary objective is to determine whether there is a statistically significant association between BMI and anaemia occurrence in this population. A quantitative correlational research design was employed, involving a purposive sample of 30 students. Data collection comprised measuring each student’s BMI and examining haemoglobin levels to assess anaemia status. The BMI was calculated based on height and weight measurements, while haemoglobin concentrations were measured using standard clinical laboratory techniques. Statistical analysis was performed using the Pearson correlation test to evaluate the strength and direction of the relationship between BMI and anaemia incidence.The results revealed a significant positive correlation between BMI and anaemia, with a Pearson correlation coefficient of 0.746 and a p-value of 0.000, indicating strong statistical significance. This finding suggests that students with higher BMI tend to have a lower risk of anaemia, highlighting the protective role of adequate nutritional status. The study confirms that BMI is a relevant factor in predicting anaemia risk among teenagers. Based on these findings, the study recommends promoting healthy nutritional habits and improving nutritional status as crucial strategies to prevent anaemia in school-aged adolescents. School health programs should emphasize balanced diets and nutritional education to address this issue effectively. Future research with larger sample sizes and longitudinal designs is encouraged to further explore causal relationships and additional factors influencing anaemia in this population.